Short- and long-term effects of rote rehearsal on ESL learners’ processing of L2 collocations - Szudarski, Pawel; Conklin, Kathy (Wiley Periodicals, 2014)
Worldwide there is thought to be around 750 million people who speak English as a foreign language (Crystal, 2003, p. 69). For these speakers the difference between make a picture and take a picture may seem arbitrary. However, use of the former is likely to influence how their second language (L2) performance is perceived (Boers, Eyckmans, Kappel, Stengers, & Demecheleer, 2006). Consequently, L2 speakers' use of collocations (“fixed, identifiable, non-idiomatic phrases and constructions”; Benson, Benson, & Ilson, 1997, p. xv) and other formulaic sequences is an important aspect of L2 competence (Wray, 2002).